Seasonal Variation and Determination of Some Heavy Metals in the Sediment from Ureje River in Ado-Ekiti, Nigeria - Okoro, H.K.; Ikumapayi, A.O.; Folorunsho, I.O. (Al-Hikmah Journal of Pure and Applied Sciences (AJPAS), 2015)
This study investigated the level of contamination of four heavy metals (chromium, cadmium, nickel, lead) in the sedimentcollected from Ureje River, Ado Ekiti, Nigeria and compared their seasonal variation (Wet and Dry seasons). The sedimentswere collected, digested and analyzed using Atomic Absorption Spectrophotometer (AAS). Two of the metals namelycadmium and nickel were not detected. During the dry season, it was observed that the mean concentrations for chromiumwere 0.36±0.08 mg/kg, 0.33±0.08 mg/kg and 0.30±0.04 mg/kg for Sites 1, 2 and 3 respectively. The mean concentration forlead during dry season at Site 1 was 0.33±0.23 mg/kg while those of Sites 2 and 3 were 0.35±0.10 mg/kg and 0.34±0.04mg/kg respectively. During the wet season, chromium levels were 0.23±0.06 mg/kg, 0.25±0.06 mg/kg and 0.21±0.03 mg/kgfor Sites 1, 2 and 3 respectively. For lead, the values recorded for Sites 1, 2 and 3 were 0.22±0.11 mg/kg, 0.30±0.10 mg/kgand 0.26±0.03 mg/kg respectively. Comparing the two seasons, the concentration of chromium was observed to be lowerthan that of lead in the dry season while the reverse was the case during the wet season. Although the concentration of themetals is unlikely to pose any risk, the presence of chromium and lead in the area calls for proper monitoring to safeguardthe health of human and aquatic lives around the area